Effect of case management on viral load in adult clients enrolled due to non-suppression in Capricorn District, South Africa: A case control study - Molebatsi Moholola; Kate Rees; Nthabiseng Motsoane; Ntsetse Kgopong; Chipo Mutyambizi (PLoS ONE, 2025)
Background Case management is a structured, client centered approach that incorporates various strategies such as employing lay counsellors to provide psychosocial and adherence support to strengthen antiretroviral (ART) adherence, improve retention in care and viral load (VL) suppression. This study aimed to evaluate the effects of case management on VL in clients enrolled due to non-suppression (> = 50 copies/ml) in Capricorn District, Limpopo Province. Methods We conducted a case control study using two datasets (1) cases were selected from case management data collected from June 2021 to November 2022 at 35 facilities and captured on the REDCap system. (2) controls were identified from TIER.Net data from facilities where case management is not available and with at least two VLs on record since June 2021. Our study was restricted to clients with an unsuppressed (> = 50 copies) VL at enrollment, over the age of 18 years and excluded clients with a missing VL at enrollment. Using similar age, gender, and VL characteristics, an equal number of clients not receiving case management was randomly sampled from the TIER.Net data. Descriptive and multivariate logistic regression analysis were used to determine the factors associated with viral suppression. Results Our final study sample consisted of 3 256 clients, half of which received case management (N = 1 628), 1084 (33%) with a first VL in study of 50–399 copies/ml, 404 (12%) 400–999 copies/ml and 1768 (54%) >1000 copies/ml. Post case management intervention results showed that 49% had a VL below 50 copies/ml amongst those receiving case management and 44% among those who did not receive case management. In the adjusted model we found that case management (Odds ratio [OR] 1.25; 95% Confidence Interval [CI] 1.08–1.44) versus no case management, 35–54 years old (1.43; 1.07–1.91) and 55+ year old (1.88; 1.35–2.61) versus 18–24-year-old increased odds of VL suppression whilst being male (0.72; 0.61–0.84) versus being female has decreased odd of VL suppression. Conclusion Close to half of the clients had a VL below 50 copies/ml after case management. Factors that increased the odds of VL suppression were case management and older age, whilst being male was associated with reduced odds of VL suppression. Differentiated services for virally unsuppressed clients would be helpful for men. Case management was associated with viral suppression in those with a starting VL > 1000 copies/ml and not for those starting with low level viremia (50–999 copies/ml).